Βeta-bloqueadores em efluente hospitalar: ocorrência, degradação por processos avançados de oxidação e identificação de subprodutos - Wilde, Marcelo Luís (2011)
β-Blockers are an important group of prescription drugs; as a consequence of the large and continuous use, they are commonly found in the environment. This study assessed, preliminary, the inherent risk of the β-blockers Atenolol, Metoprolol and Propranolol, mostly used in the University Hospital of Santa Maria (HUSM), and showed that Propranolol has high Risk Quotient (RQ) of 0.56. HPLC-FLD and SPE methodologies were developed and optimized with the aid of experimental design in order to analyze the occurrence of β-blockers in the HUSM sewage system. The average concentration for Atenolol, Metoprolol and Propranolol found for a week sampling were 2.45, 4.67 and 0.70 μg L-1 in the sewage of the Emergence; 0.95, 0.70 and 0.315 μg L-1 in the HUSM main sewage, and 1.26, 1.27 and 0.56 μg L-1 in the water course receptor, respectively, As possible remediation methodologies for the Hospital Wastewater (HWW) were investigated Advanced Oxidation Process (AOPs) such as photo-Fenton, K2FeO4, Ozonation and O3/Fe2+. The operational parameters were optimized by Response Surface Methodology (RSM). Using optimized conditions for photo-Fenton, Atenolol, Metoprolol and Propranolol were totally degraded in 5 min in aqueous solution, and the mineralization achieved 80% after 120 min of treatment. In HWW, the β-blockers were also totally degraded, however, only 26.5% of the organic matter and 38.6% of the aromaticity were removed. The ready biodegradability and toxicity of the photo-Fenton s samples were estimated by official methods, which indicated an increase in the biodegradability and toxicity. This behavior may be correlated to the formation of degradation products (DPs), relatively, more toxic. The DPs were identified with aid of Liquid Chromatography tandem Mass Spectrometry (LC-MSn). Other proposed degradation process was oxidation-coagulation using Fe(VI), which achieved above 90% degradation for Atenolol, Metoprolol and Propranolol in HWW, while only 17% COD and 60% aromaticity removal. In aqueous solution this process led to 71.7%, 24.7% and 96.5% degradation of Atenolol, Metoprolol and Propranolol, respectively. No mineralization was found, indicating the formation of DPs, identified by LC-MSn. The ready biodegradability of the post-process samples was tested and the results showed that the oxidation-coagulation with Fe(VI) increased the biodegradability. The applicability of ozonation was evaluated varying the pH (3-11) for HWW and aqueous solution. More than 95% of the β-blockers were degraded independently of the initial pH, while above 50% of the aromaticity was removed. In aqueous solution the β-blockers were degraded in 10 min treatment and the identification of the DPs were carried out for process pH 5, 7 and 9. Catalytic ozonation (O3/Fe2+) was applied to HWW and a mineralization of 49% was achieved, with 77.9% aromaticity removal. The β-blockers were totally degraded. Therefore, the present study represents a high qualified analytical information contribution concerning the occurrence of β-blockers in HWW. The studied AOPs/Fe(VI) processes demonstrated to be suitable to degrade Atenolol, Metoprolol and Propranolol. Moreover, high removal of organic matter and aromaticity were achieved by appling O3/Fe2+ process. In many aspects, this work can be considered original, in especial, by regarding the application of Ferrate(VI) and Catalytic Ozonation to the degradation of β-blockers in HWW.